Question
upstudy study bank question image url

Solve for all values of x : \[ \sqrt{3 x}+2=\sqrt{6 x-1} \]

Ask by Burns Savage. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x = \frac{25}{3} \) and \( x = 8.\dot{3} \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Beyond the Answer

To solve the equation \( \sqrt{3x} + 2 = \sqrt{6x - 1} \), we start by isolating one of the square root terms: 1. Move 2 to the other side: \[ \sqrt{3x} = \sqrt{6x - 1} - 2 \] 2. Square both sides to eliminate the square roots: \[ (\sqrt{3x})^2 = (\sqrt{6x - 1} - 2)^2 \] This simplifies to: \[ 3x = (6x - 1) - 4\sqrt{6x - 1} + 4 \] Which further simplifies to: \[ 3x = 6x + 3 - 4\sqrt{6x - 1} \] 3. Rearrange the equation to isolate the square root: \[ 4\sqrt{6x - 1} = 6x + 3 - 3x \] Simplifying gives: \[ 4\sqrt{6x - 1} = 3x + 3 \] 4. Divide both sides by 4: \[ \sqrt{6x - 1} = \frac{3x + 3}{4} \] 5. Square both sides again: \[ 6x - 1 = \left( \frac{3x + 3}{4} \right)^2 \] This expands to: \[ 6x - 1 = \frac{(3x + 3)^2}{16} \] Simplifying the right side: \[ 6x - 1 = \frac{9x^2 + 18x + 9}{16} \] 6. Multiply everything by 16 to eliminate the fraction: \[ 16(6x - 1) = 9x^2 + 18x + 9 \] Simplifying gives: \[ 96x - 16 = 9x^2 + 18x + 9 \] 7. Rearranging the equation: \[ 0 = 9x^2 - 78x + 25 \] We can now use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 9, b = -78, c = 25 \): Calculate the discriminant: \[ b^2 - 4ac = (-78)^2 - 4 \cdot 9 \cdot 25 = 6084 - 900 = 5184 \] Now applying the quadratic formula: \[ x = \frac{78 \pm \sqrt{5184}}{18} \] Since \( \sqrt{5184} = 72 \): \[ x = \frac{78 \pm 72}{18} \] 8. Solving for the two possible values of \( x \): \[ x_1 = \frac{150}{18} = \frac{25}{3} \] \[ x_2 = \frac{6}{18} = \frac{1}{3} \] Finally, we check for extraneous solutions by substituting back into the original equation: For \( x = \frac{25}{3} \): \[ \sqrt{3 \cdot \frac{25}{3}} + 2 = \sqrt{6 \cdot \frac{25}{3} - 1} \implies \sqrt{25} + 2 = \sqrt{50 - 1} \implies 5 + 2 = \sqrt{49} \implies 7 = 7 \quad \text{(valid)} \] For \( x = \frac{1}{3} \): \[ \sqrt{3 \cdot \frac{1}{3}} + 2 = \sqrt{6 \cdot \frac{1}{3} - 1} \implies \sqrt{1} + 2 = \sqrt{2 - 1} \implies 1 + 2 = \sqrt{1} \implies 3 = 1 \quad \text{(not valid)} \] Thus, the only solution is: \[ \boxed{\frac{25}{3}} \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy